Understanding migraine and other headaches - Tepper, Stewart J. (Understanding health and sickness series., 2004)
Health & SICKNESS -- Consumer Health -- & . In the United States, eighteen percent of women, six percent of men, and four percent of children suffer from migraine headaches. All races are affected, although, for reasons which are unknown, whites are more likely than African Americans to be afflicted with the condition, and Asian Americans are least often migraine sufferers. Migraine is an inherited condition-many families can trace it back for generations-and it has enormous economic and social consequences, both to individual sufferers, and to the society as a whole. The cost to the U.S. societ.